Incidence of hepatocellular carcinoma in untreated subjects with chronic hepatitis B: a systematic review and meta-analysis - Raffetti, Elena; Fattovich, Giovanna; Donato, Francesco (Liver international, 2016)
Background & aims In the natural history of hepatitis B virus (HBV) chronic infection, the hepatocellular carcinoma (HCC) risk is unclear. We assessed incidence and predictors of HCC by a systematic review and meta‐analysis. Methods We included longitudinal studies and randomized controlled trials assessing HCC incidence in untreated patients with HBV chronic infection. Incidence rates and their 95% confidence intervals were extracted by each study and pooled together in random effects models. Results Sixty‐six studies were included with a total of 347 859 patients. According to liver disease status, the summary incidence rates were in Europe, North America and East Asia, respectively: (a) asymptomatic carriers: 0.07 (95% confidence interval: 0.05–0.09), 0.19 (0.07–0.31) and 0.42 (0.21–0.63) per 100 person‐years, respectively; (b) inactive carriers: 0.03 (0.0–0.10), 0.17 (0.02–0.62) and 0.06 (0.02–0.10), respectively; (c) chronic hepatitis: 0.12 (0.0–0.27), 0.48 (0.22–0.91) and 0.49 (0.32–0.66), respectively; (d) compensated cirrhosis (Child–Pugh A): 2.03 (1.30–2.77), 2.89 (1.23–4.55) and 3.37 (2.48–4.26) respectively. Multivariate meta‐regression showed a significant increase in incidence rates for age, and for status of a symptomatic carrier, chronic hepatitis and compensated cirrhosis compared to inactive carrier, but not for geographical area after adjusting for age. An increase in the incidence rates was also observed for alcohol intake ≥60 g/dl, HBV genotype C with respect to B and HBV‐DNA serum levels >2000 IU/ml, in Asian studies. Conclusions Hepatocellular carcinoma risk in untreated subjects with HBV chronic infection is strongly related with age and liver disease status.